Tanggung Jawab Direksi Dalam Penyampaian Laporan Keuangan Overstatement - Tionardi, Cecil Natasya (Tribuere, 2022)
A case of overstatement of AISA's financial report by raising the debt value to improve the company's performance detrimental to investors. Normative type research, descriptive research nature, secondary data sources, library study data collection, qualitative data analysis and methods of deductive conclusion. AISA management is responsible for violating fiduciary duty by performing ultra vires actions, liability imposed according to piercing the corporate veil. Responsibility in accordance with Rule 3 paragraph (2), Article 69 paragraph (3) together with 97 paragraph (4) and Article 69 subparagraph (4) together with Article 97 subsection (4) (5). The judge's verdict is not maximum, in UUPM Article 104 the maximum can be 10 years in prison and a fine of 15 billion each.